(3GdJVNe GdeGdj hGdSjGSI GdVQjHjI aj ehGLgI GdJVNe GdGbJUGOj (B: s (3OQGSI JWHjbjI Ydi eUQ (B/ s - (3eMeO MGJe YHO GdcQjes; (3YGWa UObjs; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb (B- (3LGeYI GdbGgQI,s, 1984)
(3JSJgOa GdOQGSI Edi YbO ebGQfI Hjf hSjdJjf ef hSGFd YdGL GdJVNe hgeG GdJVNe GdeGdj hGdSjGSI GdVQjHjI hjQLY GdSHH aj gPG GdGNJjGQ Edi GNJdGa WHjYI heLGd hBKGQ cd ef gGJjf GdhSjdJjf aGdhSjdI GdChdi JaJYd JVNeG eMOhOG cj JSJWjY YdGL GdJVNe GdQFjSj hef Ke dG jhLO Cj GSJNOGe dWGbGJ Ch ehGQO aYdjg; hHPdc JYJHQ hSjdI ZjQ MbjbjI aj Mjf Cf GdhSjdI GdKGfjI JYJeO Ydi GdbOQGJ GdaYdjI hGdMbjbjI GdeJhaQI dOi GdOhdI(B. (3GdSjGSjI GdVQjHjI JYJHQ hSjdI PGJ COhGJ hUhQ eJYOOI JLYdgG edGFeI ddGSJNOGe aj cd GdeLJeYGJ GdJj JYGfj ef GdJVNe(B. (3hGdSjGSI GdVQjHjI JJLg eHGTQI YfO GdGSJNOGe GdSdje dgG ceG HjfG Edi YdGL CSHGH GdJVNe Ohf Cf jfJL YfgG CjI BKGQ JVNejI NWjQI HYcS GdJVNe GdeGdj GdPj jJLg HWHjYJg Edi GdYdGL e NdGd eG jMOK ef BKGQ JVNejI hef gfG JHQR NWhQI GSJNOGeg, aEPG cGfJ GdSjGSI GdYQHjI JJLg Edi Ndb ONhd LOjO JPcj GdJVNe GdehLhO Cf GdSjGSI GdYQHjI bGOQI Ydi JMbjb GfJbGd YhGed GdEfJGL ddeLGdGJ GdJj JYGfj ef GNJdGd LGfH GdYQV Ohf GddLhA Edi QaY CKeGfgG HYcS GdJVNe GdeGdj GdPj jYJHQ QaY GdCKeGf gh GdCSdhH GdCSGSj dJMbjb gPG GdGfJbGd hgh eG jfYcS Ydi fabGJ GdEfJGL Cf GdJchjf GdQCSeGdj GdPj JSJWjY GdSjGSI GdYQHjI JMbjbg jYJHQ hSjdI Jehjd MbjbI dRjGOI eQhfI dLgGR GdEfJGL (B. (3Cf GdSjGSI GdYQHjI bGOQI OGFeG Ydi JUMjM MQcI ONhd hGdGSJKeGQ ef NdGd COhGJgG GdeNJdaI HUhQI OhQjI HYcS GdJVNe GdeGdj GdPj jUYH ef JMbjb GdSjWQI Ydi MQcI GdONhd hGdGSJKeGQ aVdG Yf chf COhGJ JMbjb gPg GdSjWQI HYjOkG Yf eJfGhd HOA GdJVNe GdeGdj (B. (3Ef GdSjGSI GdVQjHI YfO ehGLgJgG ddJVNe JLO dgG WQjbI aj GdMO ef GdWdH eKdeG JLOg aj JMbjb GdRjGOI(B.s
(3CWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI, cdjI GdMbhb, bSe GdeGdjI GdYGeI hGdJTQjY GdVQjHj (B1984.s
(3jTJed Ydi EQLGYGJ HHdjhLQGajI(B: (3UaMI (B659-691.s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdVQGFHs; (3GdQCSeGdjIs; (3GdGTJQGcjIs; (3GdSjGSI GdVQjHjI s; (3GdGbJUGO Gdbhejs; (3GdfbO Gdhgejs; (3GdeQhfI GdVQjHjIs; (3GdWGbI GdVQjHjIs; (3GdJVNes; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdJTQjY GdVQjHjs